Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1088/0957-0233/21/10/105105
|View full text |Cite
|
Sign up to set email alerts
|

An outlier correction procedure and its application to areal surface data measured by optical instruments

Abstract: An outlier correction procedure for areal surface topography data based on surrounding data for outlier detection and correction is reviewed. The outlier detection is based on the median relative height of the surrounding data within a defined detection window. The threshold value is calculated from a cumulative probability curve of the medians of all data points. The detection window size is selected based on the size of the largest outlier cluster observed on the topography data. The application of the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…However, it will fail when applied to data with clustered outliers since these outliers can result in biased medians. Ismail et al [8] developed an optimized median filter. The outlier detection is based on the median relative height of the surrounding data within a defined detection window.…”
Section: B Post-process Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it will fail when applied to data with clustered outliers since these outliers can result in biased medians. Ismail et al [8] developed an optimized median filter. The outlier detection is based on the median relative height of the surrounding data within a defined detection window.…”
Section: B Post-process Approachesmentioning
confidence: 99%
“…In addition to measurement noise, optical measurement techniques can often produce unmeasured or faulty points and outliers. Outliers are presented as sudden sharp jumps compared to the surrounding data and occur at certain localities on the surface [8]. In ISO 16610-1 [9], an outlier is defined as a local portion in a data set that is not representative, or not typical, for the partitioned integral feature.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high sampling frequency and limited reflectivity of the rubber surface, outliers, which have unreasonably high and low values compared to the surrounding data, were observed in the raw data. To eliminate those outliers, a filter based on the cumulative probability neighbor median (Ismail et al, 2010) was used to process data. The filtered signal shows clear peaks when the tire was being deformed by the road (Fig.…”
Section: Data Processingmentioning
confidence: 99%
“…Outliers are errors which must be treated selectively. In the current study, an outlier correction procedure reported in [25] which the outliers detection is based on median of neighbouring relative height, is employed with the largest outlier cluster is defined as 5 Â 5 pixels and detection level L is 1.1. The height information of identified outliers is deleted and replaced with an artificial value based on the weighted average of available normal data points on 8 equiangular directions.…”
Section: Outliers Correctionmentioning
confidence: 99%